Controlling the Solubility, Release Rate and Permeation of Riluzole with Cyclodextrins - Tatyana Volkova; Olga Simonova; German Perlovich (MDPI AG, 2024)
Riluzole (RLZ), a sodium channel-blocking benzothiazole anticonvulsant BCS class II drug, is very slightly soluble in aqueous medium. To improve aqueous solubility and modulate dissolution rate and membrane permeability, complex formation of RLZ with two cyclodextrin, α-cyclodextrin (α-CD) and sulfobutylether-β-cyclodextrin (SBE-β-CD), was studied. The stability constants demonstrated a greater affinity of SBE-β-CD towards RLZ compared to α-CD. A solubility growth of 1.7-fold and 3.7-fold with α-CD and SBE-β-CD, respectively, was detected in the solutions of 1% cyclodextrins and accompanied by the permeability reduction. For 1% CD solutions, several biopolymers (1% w/v) were tested for the membrane permeability under static conditions. The synergistic positive effect of α-CD and polymer on the solubility accompanied by unchanged permeability was revealed in RLZ/α-CD/PG, RLZ/α-CD/PEG400, and RLZ/α-CD/PEG1000 systems. Solid RLZ/CD complexes were prepared. Dynamic dissolution/permeation experiments for the solid samples disclosed the characteristic features of the release processes and permeation rate through different artificial membranes. The maximal permeation rate was determined across the hydrophilic semi-permeable cellulose membrane followed by the lipophilic PermeaPad barrier (model of intestinal and buccal absorption) and polydimethylsiloxane-polycarbonate membrane (simulating transdermal delivery way). Different mode of the permeation between the membranes was estimated and discussed.